2020
DOI: 10.1016/j.conbuildmat.2020.119587
|View full text |Cite
|
Sign up to set email alerts
|

Neutron radiography to study the water ingress via the interlayer of 3D printed cementitious materials for continuous layering

Abstract: h i g h l i g h t sContinuous layering results in no preferential water ingress at the interfaces. An increased printing speed shows preferential water ingress through the sample sides. 3D printed specimens with SAPs have an increased water uptake ability and speed. By increasing the layer amount, the upper layer has the highest water uptake capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Even though such techniques are promising, automating the process and controlled deposition of the adhesives without causing rupture or tear to the substrate layer can be challenging. The addition of internal curing agents like superabsorbent polymers has also shown promise in this regard by preventing the moisture loss at the interface [125][126][127]. In the study by Wang et al [128], epoxy resin and chloroprene latex were added to the concrete during mixing.…”
Section: Materials Behaviour In the Hardened Statementioning
confidence: 99%
See 2 more Smart Citations
“…Even though such techniques are promising, automating the process and controlled deposition of the adhesives without causing rupture or tear to the substrate layer can be challenging. The addition of internal curing agents like superabsorbent polymers has also shown promise in this regard by preventing the moisture loss at the interface [125][126][127]. In the study by Wang et al [128], epoxy resin and chloroprene latex were added to the concrete during mixing.…”
Section: Materials Behaviour In the Hardened Statementioning
confidence: 99%
“…10. Capillary water uptake quantified using neutron radiography has also been useful in assessing the transport properties of printed concrete [126,127]. For samples with a larger time gap, Schröfl et al [126] showed that quick water ingress due to capillary suction occurred at the layer interfaces while a very low water uptake was observed in the bulk matrix.…”
Section: Pore Structure and Transport Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Linked to shrinkage-and durabilityrelated issues, the 3D printing of cementitious materials still faces some problems such as autogenous shrinkage, which may be counteracted using SAPs. Continuous layering of printed specimens with SAPs (Figure 5.1) already proved to be successful [19]. This is a recent field of study and many parameters may be investigated.…”
Section: Changing the Rheology By Absorbing Mixing Watermentioning
confidence: 99%
“…In addition, the workability can be controlled, which is interesting for 3D printing technologies using cementitious materials [19,20]. Linked to shrinkage-and durabilityrelated issues, the 3D printing of cementitious materials still faces some problems such as autogenous shrinkage, which may be counteracted using SAPs.…”
Section: Changing the Rheology By Absorbing Mixing Watermentioning
confidence: 99%